ANALYSIS OF THE IDEAS OF PRESIDENTIAL CANDIDATES “PS” IN INCREASING THE NUMBER OF EXCELLENT SCHOOL IN THE 3 T REGION - Hudjolly Hudjolly; Sri Suharti; Heriyanto Heriyanto; Fika Fibriyanita; Riska Aulia Noor (ITB AAS Indonesia Surakarta, 2024)
Abstract The policy idea of increasing the number of superior schools in 3T areas has the good aim of equalizing education and creating golden generations in the future. However, this idea has a number of threats and challenges that must be faced, including the amount of the budget, the readiness of teaching staff, and the readiness of the local community. If these threats and challenges are not faced properly, it will create an unsustainable project. This research aims to analyze these policy ideas. This research is qualitative research with a descriptive approach that uses secondary data obtained from books, trusted websites, and indexed scientific articles. The data used was analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions. Keywords: Idea, Excellent School, 3T Region